Descriptive Analysis of Language Style Used by Radio Announcer - Liya Umaroh; Lily Tania Innezaputri (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
The aim of this study was to find out the types of language styles which were applied by the Gajah Mada group’s radio announcer using descriptive qualitative research method along with observation and interview as the data collection. The number of informants were 11 people, consisting of eight radio announcers and three people from radio announcer teams. The results of this study indicated that the three radios used the language style joint, which includes honesty, politeness and attractiveness. Furthermore, language styles were found on the types of language styles that can be viewed from non-language perspective according to place and audience. Then in terms of language, based on the choice of words, namely official, informal and conversational in accordance to the choice of tone using simple and medium tones, and based on the sentence structure used climax. The use of this language style is supported by the ability of public speaking by the announcer in delivering information to listeners.